Consumer Satisfaction Analysis That Affected Product Quality, Word Of Mouth, With Price Perception As a Mediation Variable - Bunga Rizka Amalia; Aris Budiono (Cita Konsultindo Research Center, 2022)
This study aimed to determine the effect of Product Quality, Word of Mouth on Consumer Satisfaction through Price Perception in Nasi Kulit Bisa Boss Cibinong. Data were obtained in March 2021 with as many as 100 respondents with 20 respondents for the Validity test and Reliability test and 80 respondents for the path analysis test, sampling using the Roscoe technique. They were using path analysis techniques to see the direct and indirect path of the independent variable to the independent variable. This study resulted in the following conclusions: Product Quality has a significant effect on Price Perception, Word of Mouth has a substantial effect on Price Perception, Word of Mouth has a considerable effect on Consumer Satisfaction, and Product Quality has no significant effect on Consumer Satisfaction, Price Perception has a substantial effect on Consumer Satisfaction. Product Quality has a considerable effect on Price Perception through Consumer Satisfaction. Word of Mouth has a significant effect on Price Perception through Consumer Satisfaction.